ChemInform Abstract: Friedel—Crafts Acylation Reactions Using Esters. Issue 17 (4th April 2013) - Chavan, Subhash P.; Garai, Sumanta; Dutta, Achintya Kumar; Pal, Sourav
Abstract This method can be used for intermolecular as well as intramolecular Friedel‐Crafts acylations, e.